The Corner of the Living : Ayacucho on the Eve of the Shining Path Insurgency - La Serna, Miguel (Book collections on Project MUSE., 2012)
Interest remains high in the story of the Shining Path, the Maoist guerrilla insurgency founded in Peru in the late 1960s. Miguel La Serna's history of key roles played by Peru's indigenous peoples in the conflict adds a major new dimension to our understanding of Peru's war, especially with La Serna's fresh, unique emphasis on the years leading up to the peak years of violence from 1980-1992. On a broader level, La Serna's work drives home how localized, culturally particular perspectives contributed to the internationally significant political events in Peru that shaped much of the world during the Cold War.